Teratogenic effects of Khat (Catha edulis) in New Zealand rabbit - Abdul-Mughni, Aref Saleh; El-Nahla, Sanaa Mokhtar; Hassan, Said Ahmed; Dessouki, Amina Ali (Journal of Advanced Veterinary and Animal Research, 2018)
Objective: The present study was carried out to evaluate morphometric and histopathological abnormalities during organogenesis in liver, kidney, brain, spinal cord, heart, Lung, digestive tract and spleen in rabbit feti in response to oral administration of Khat prepared from leaves of khat tree (Catha edulis). Materials and methods: The current work was carried out with apparently healthy adult New Zealand rabbits (n=27; 3 males and 24 females) weighing 2.5±0.5 Kg. The female rabbits were divided into four equal groups. Three goups (low, medium and high dose groups) were treated with Khat. The groups were given 3 mL, 6 mL and 12 mL extract/Kg bwt once daily from day 8 to 18 of gestation, respectively. The control group was given distilled water only. All females were slaughtered on day 28 of gestation. Visceral organ were subjected for histopathological examinations. Results: Khat was found to be associated with hepatotoxicity and nephrotoxicity in rabbits. The kidney of feti of treated dams showed subcapsular hemorrhages along with mild vacuolar degeneration of some renal tubular epithelium. Glomeruli were atrophied, and moderate degenerative changes were observed in renal tubular epithelium and hemorrhages between renal tubules. The liver of the feti showed vacuolar degeneration, necrotic hepatitis, congestion of central veins and hepatic sinusoids, pyknotic clumped nuclei, hemorrhages, edema with atrophy of some hepatocytes, and hyperplasia of Megakaryocytic cells. The Khat also harmed the brain causing hemorrhage, edema, degenerative changes, swelling and necrotic changes of some nerve cells as well as supporting cells. The spinal cord was affected showing degeneration of nerve fibers in white matter and some neurons in grey matter. The heart of treated feti showed congestion of epicardial blood vessels and diffuse degeneration of heart muscles. Lung and alimentary tract only showed congestion of blood vessels. Conclusion: Prenatal exposure of Khat in rabbit induces harmful effects in defferent visceral organs including liver, kidney, brain, spinal cord, spleen, intestine, heart and lung. http://doi.org/10.5455/javar.2018.e242